DAYA DUKUNG DAN DAYA TAMPUNG WISATAWAN SITUS PERAHU KUNO DESA PUJULHARJO KECAMATAN REMBANG KABUPATEN REMBANG - Putra, Kiswanto Syah; Syah Putra, Rizal Rizal Ichsan (Environmental Science Program, Ivet University, 2023)
In the tourism sector, the concepts of carrying capacity and carrying capacity have a significant role in maintaining a balance between economic growth and environmental preservation. Carrying capacity refers to the capability of a tourist destination or tourism area to manage the number of visitors without disturbing the natural ecosystem, cultural heritage and local social dynamics. Conversely, capacity describes the maximum number of tourists that can be received by a destination without reducing the quality of the tourist experience or disrupting the balance of ecosystems and local community interactions. An analysis of carrying capacity and carrying capacity in the context of tourism includes measuring and assessing the various factors that influence the relationship between visitors, the environment and the local community. These factors include accommodation infrastructure, means of transportation, waste management, water sources, as well as social dimensions such as local customs and cultural values. The main aim of this analysis is to avoid